Seroprevalence of infection by Trypanosoma cruzi and associated factors in the adult population in a highly endemic area of Arequipa, Perú - Sánchez Sánchez, Yván (2007)
Objective: determine the seroprevalence of infection by T. cruzi in the population above age 15 in the valley of Vítor, describing general characteristics and the presence of associated factors. Materials and Methods: 499 people above age 15 were randomly selected; epidemiological information was obtained through a survey. The diagnosis of the disease was made by ELISA and IIF. Results: the seroprevalence for Chagas reactivity was 10,2%, 10,35% in women and 10,0% in men. The median of age of the typical Chagas disease patient was 42±17,9, his/her time of residence in Vítor was 34±15,9 years; 51,0% had been born in the valley of Vítor. Agricultural workers made up 41,2%, of the general population, and 51,0% have a high school education. Rustic housing materials were associated with the infection. Conclusions: the valley of Vítor is an endemic area for Chagas disease. The infection equally affects men and women. The typical infected patient is native to the valley of Vítor, works in agriculture and has secondary level education. Rustic building materials is associated to the infection by T.cruzi because it favors the presence of the vector.